2003
DOI: 10.1097/01.ta.0000064452.37534.29
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline Improves Tissue Oxygenation and Reduces Systemic and Pulmonary Inflammatory Response Caused by Hemorrhagic Shock

Abstract: HTS improved tissue oxygenation and perfusion and reduced systemic and pulmonary inflammatory responses compared with IS in the treatment of HeS in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 35 publications
0
24
0
5
Order By: Relevance
“…In the sham group, rats only received anesthesia, cannulation, heparinization, and observation. In the fluid resuscitation phase, rats in the NS resuscitation group received 0.9% (9 g/L) NaCl infusion for a 3:1 ratio against the blood loss volume (Gurfinkel et al, 2003;Alam et al, 2004;Barros et al, 2011;Maier and Alam, 2011). The HTS group received 6.0 ml/kg body weight of 7.5% (0.075 g/ml) NaCl solution for a 1:5 ratio against blood loss volume (Murao et al, 2003a;2003b).…”
Section: Grouping Of Animalsmentioning
confidence: 99%
“…In the sham group, rats only received anesthesia, cannulation, heparinization, and observation. In the fluid resuscitation phase, rats in the NS resuscitation group received 0.9% (9 g/L) NaCl infusion for a 3:1 ratio against the blood loss volume (Gurfinkel et al, 2003;Alam et al, 2004;Barros et al, 2011;Maier and Alam, 2011). The HTS group received 6.0 ml/kg body weight of 7.5% (0.075 g/ml) NaCl solution for a 1:5 ratio against blood loss volume (Murao et al, 2003a;2003b).…”
Section: Grouping Of Animalsmentioning
confidence: 99%
“…The control group animals during the experiment were simply mechanically ventilated and Ringer lactate was administered intravenously at a rate of 0.2 ml/kg/min. Animals were observed until 120 min of resuscitation since at that time-period the effect of shock resuscitation in the BAL fluid and lung histology is detectable (Gurfinkel et al 2003;Powers et al 2005). At the end of the experiment, animals were prepared for BAL procedure; chest was opened by midline sternotomy, exsanguination followed by cardiac puncture and euthanasia was performed synchronously with 150 mg of pentobarbital given intravenously.…”
Section: Protocolmentioning
confidence: 99%
“…Likewise, a systemic review of animal studies [5] has also shown a lower risk of death in animals resuscitated to hypotensive levels than in animals resuscitated to normotensive levels (P \ 0.00001). The small volume resuscitation with fluids such as hypertonic saline [6] or albumin 25% [7] has similarly shown a higher survival rate compared with infusion of isotonic fluids.The approach of attempting to lessen reperfusion injury by adjusting the inspired O 2 may apply either before [8] or during [9-12] resuscitation. As far as the first case is concerned, the impact of inspired oxygen concentration on tissue oxygenation (tPO 2 ) in the absence of resuscitation was the subject of a study from Dyson et al [8], published in this issue of the journal.…”
mentioning
confidence: 99%
“…Recently, the importance of limited resuscitation [4][5][6][7] has been widely acknowledged. Patients with penetrating truncal trauma, in which resuscitation was delayed, had a higher survival rate to discharge (70%) compared with promptly resuscitated patients (62%, P = 0.04) [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation